Ruptured dermoid cyst of ovary developing into chronic peritonitis; a rare complication diagnosed by contrast CT: A case study. (October 2022) - Rai, Kalpana; Dhakal, Binaya; Shahi, Sunil; Pant, Sujit; Sapkota, Suhail; Timilsina, Bibek
Abstract: Introduction: Dermoid cyst also called Mature cystic teratoma is the most common ovarian germ cell tumor of pre-menopausal females, composed of skin, hair, teeth, and sebum covered by thick fibrous tissue. It can present with complications like torsion, rupture, infection, and autoimmune hemolytic anemia. The case highlights the role of imaging in the diagnosis of ruptured dermoid cyst which can have subtle clinical features. Case Presentation: Herein we present a case of 53 years multiparous postmenopausal female who presented with lower abdominal pain. Examination findings at presentation were normal. 2 years back patient was evaluated for the abdominopelvic mass which was diagnosed radiologically as an ovarian dermoid cyst. This time, Ultrasonography (USG) of the abdomen and pelvis followed by Contrast-enhanced computed tomography (CECT) of the abdomen and pelvis revealed the features consistent with a ruptured dermoid cyst. Exploratory laparotomy and histopathological examination of the specimen confirmed the diagnosis. Clinical Discussion: Rupture of a dermoid cyst is a very infrequent complication. Following rupture patient may present with peritonitis which may be acute or chronic. Chronic peritonitis may not show any clinically distinguishable features such that the clinical diagnosis of the rupture dermoid cyst is difficult to make. The radiological assessment helps to make an accurate diagnosis so that appropriate surgical intervention can be instituted. Conclusion: Following the rupture of the dermoid patients may progress to a stage of chronic peritoneal inflammation. At this stage, the radiological assessment may be crucial for appropriate diagnosis and thus further management. Highlights: Dermoid cyst is the most common ovarian germ cell tumor of pre-menopausal females. Rupture of an ovarian dermoid cyst is a rare complication. Rupture of the dermoid cyst may present with very subtle and marginal symptoms that are not clinically distinguishable. The ruptured teratoma can be accurately diagnosed by the contrast CT and hence the appropriate management can be made.